Analisis Perhitungan Titik Impas Produk Susu Murni, Yoghurt, dan Keju Mozzarella - Hanifa Khoirunnisaa Heryanto; Arwan Gunawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Micro, Small and Medium Enterprises (MSMEs) as economy pillars in Indonesia must have a business planning. Calculation of the break-even point can be used to determine the minimum sales of products, prepare sales and profit budget, and monitor business performance. This study aims to help SMEs Sapi Mandiri Cipageran in calculating the break-even point. This type of research is qualitative with descriptive analysis. Data obtained from observation, direct interviews and documentation. The results showed that break-even point in pure milk products is 17,7 liters per day or 530 liters per month for one cow. In rupiah, sales reach the break-even point in the amount of Rp33.909.238. Then for yogurt products, the break-even point value is 20 bottles of yogurt or equal to Rp159.186. Meanwhile, the break-even value of mozzarella cheese products is 10 units or equal to Rp1.016.667.